Assessing the effects of diabetes mellitus on the monocyte-to-lymphocyte ratio and the QuantiFERON-TB gold plus assays for tuberculosis treatment monitoring: a prospective cohort study - Ranaivomanana, Paulo; Razafimahefa, Arimanitra; Ndiaye, Mame; Razafimahatratra, Crisca; Ramamonjisoa, Haja; Herindrainy, Perlinot; Raherison, Mamy; Raherinandrasana, Antso Hasina; Rakotonirina, Julio; Hoffmann, Jonathan; Ratovoson, Rila; Rakotosamimanana, Niaina (Frontiers in Immunology, 2025)
Diabetes mellitus (DM) is an important risk factor for the development of active tuberculosis (TB). QuantiFERON-TB Gold Plus (QFT-P), white blood cell count (WBC) assays and monocyte-to-lymphocyte ratio (MLR) reflect the inflammatory reactions associated with TB and offer the potential to monitor TB treatment to allow a better management of the disease. The aim of this study was to assess the influence of DM on the respective performances of QFT-P and WBC assays in their capacities to monitor the treatment of drug-sensitive pulmonary TB (TBP). The QFT-P and WBC were prospectively compared between TB patients with and without DM at inclusion (D0), at the end of treatment (M6) and two months after the end of treatment (M8). After laboratory measurement of glycated hemoglobin (HbA1c), the patients were categorized into two groups: the TBP (n=43) and the TBDM (n=30) groups. The TBDM patients were characterized by an elevated Mycobacterium tuberculosis-specific QFT-P IFN-γ response after TB treatment compared to the TBP group (p<0.001 and p<0.05, respectively, after TB1 and TB2 antigens stimulation). A significantly higher proportion of positive QFT-P tests was observed in the TBDM group compared to the TBP group (91.3% vs 64.1%) at the end of the treatment (p=0.03). MLR analysis showed a decrease of MLR value after TB treatment for both diabetic and nondiabetic TB patients (p<0.001 and p<0.05). These data reflected from immune-host based tests used to monitor the TB treatment, seemed to further suggest that TB with concomitant DM is associated with a persistent inflammatory response after TB treatment.